Analisis Kemampuan Spasial dan Respons Siswa terhadap Implementasi E-Modul Pembelajaran Inkuiri Terintegrasi Laboratorium Virtual (IL-VIL) pada Konsep Sistem Peredaran Darah Manusia - Arindra Alfarizi; Suciati; Sri Yamtinah (Jurnal Penelitian Pendidikan IPA, 2024)
The human cardiovascular system presents challenges for students due to its abstract and complex nature. Spatial ability plays a crucial role in understanding the 3D structures and dynamic processes within the system. Integrating e-modules with virtual laboratories offers a promising method to enhance students' visualization and comprehension of these abstract concepts. This research aims to analyze the spatial ability outcome and student’s responses of E-Module Il VIL in Human Cardiovascular System. A descriptive quantitative approach was used, utilizing surveys, observations to gather data on students' experiences and the quesionary test of spatial abilities following their use of the E-Module IL-VIL in Human Cardiovascular System concept. The research sample consisted of 31 students in Surakarta City participated in the learning process using thee E-Module IL-VIL. The results indicated significant improvements in students' spatial abilities, particularly 28.83% improvement in mental rotation, 35.89% in spatial orientation, and 19.74 in spatial visualization. A total of 96.8% of students agreed that the IL-VIL accibility, engaging, flexible, and beneficial, while only 3.2% disagreed. These findings demonstrate the effectiveness of E-Module IL-VIL as an educational tool for enhancing students' spatial ability and comprehension of complex scientific subjects.